Reliability, validity and responsiveness of the Slovenian version of the Patient Evaluation Measure (PEM-Slo) in patients with wrist and hand disorders - Bojnec, Vida (Zdravstveno varstvo, 2023)
Introduction: The Patient Evaluation Measure (PEM) is a region-specific patient reported outcome measure (PROM) for hand and wrist disorders, first introduced in English for patients with hand surgery in 1995. The purpose of the study was to assess the psychometric properties of the translated and cross-culturally adapted Slovenian version of PEM (PEM-Slo). Methods: The study was designed as a single-centre observational prospective study conducted from July 2020 to March 2021. The psychometric evaluation was performed on fifty-one patients with miscellaneous hand and wrist disorders. Reliability was tested for internal consistency and test-retest reliability. Convergent and divergent validity, responsiveness, floor and ceiling effect, and interpretability with the determination of minimal detectable change (MDC) and minimal clinically important difference (MCID) were assessed. Results: The PEM-Slo has excellent internal consistency (Cronbach’s ? 0.932) and good to excellent test-retest reliability (intraclass correlation coefficient=0.874). Convergent validity was proved with high to moderate correlations of PEM-Slo with DASH, grip strength and self-care, usual activities, and pain EQ-5D-5L subscales, whereas no correlation of PEM-Slo with EQ-5D-5L mobility and anxiety/depression subscale confirmed divergent validity. The PEM-Slo responsiveness was high (standardised response mean=1.42, effect size=1.25). MDC was 18.01 and MCID was 17.31. No floor or ceiling effect was found. Conclusion: The PEM-Slo is a reliable, valid and responsive PROM for Slovenian-speaking patients with hand and wrist disorders.
Keywords: hand; patient-reported outcomes; PEM; psihometrične lastnosti; psychometric properties; roka; samoocenjevalna lestvica; wrist; zapestje